2010
DOI: 10.1021/jp101146a
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Mass Spectrometry of the Exothermic Reaction between Nanoaluminum and Metal Oxides: The Role of Oxygen Release

Abstract: In this work, heterogeneous nanocomposite reactions of Al/CuO, Al/Fe2O3 and Al/ZnO systems were characterized using a recently developed T-Jump/time-of-flight mass spectrometer. Flash-heating experiments with time-resolved mass spectrometry were performed at heating rates in the range of ∼105 K/s. We find that molecular oxygen liberated during reaction is an active ingredient in the reaction. Experiments also conducted for neat Al, CuO, Fe2O3, and ZnO powders show that the oxygen are produced by decomposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
86
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 31 publications
(66 reference statements)
9
86
1
1
Order By: Relevance
“…For some thermites, such as Al/CuO, experiments using time-resolved mass spectrometry have measured significant O 2 release under rapid heating [32,33].T he formation of gaseous intermediates and their contribution to the pressurization may suggest why as ystem such as Al/MoO 3 , which is thermodynamically predicted to produce approximately only ap ercent of the gas that Al/CuO or Al/Bi 2 O 3 does, reacts rapidly and generates pressure as many other thermites.…”
Section: Introductionmentioning
confidence: 99%
“…For some thermites, such as Al/CuO, experiments using time-resolved mass spectrometry have measured significant O 2 release under rapid heating [32,33].T he formation of gaseous intermediates and their contribution to the pressurization may suggest why as ystem such as Al/MoO 3 , which is thermodynamically predicted to produce approximately only ap ercent of the gas that Al/CuO or Al/Bi 2 O 3 does, reacts rapidly and generates pressure as many other thermites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that organic or inorganic nano/microparticles deposited on metal surfaces could be heated to a wide range of surface temperature (from $100°C to $1800°C) at a rate as high as $10 6°C /s [26][27][28][29][30][31]. In those studies, the heating time could be controlled with millisecond precision and the heating rate could be accurately tuned from $10 3°C /s to $10 6°C /s, allowing the application of uniform temperature to a deposited particle layer up to 5 lm thick [29] which exceeds the dimensions of a monolayer of bacterial spores.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the energy or temperature required to initiate the thermite reaction is relatively high. Williams et al found the ignition temperature of Al and Fe 2 O 3 was 800 K-950 K by experiment [18], but Zhou et al concluded that the ignition temperature of Al and Fe 2 O 3 was 1100 K using T-Jump/time-of-flight mass spectrometer [10], while Fan et al discovered that the exothermic peak of DSC curves of Al and Fe 2 O 3 powder mixture appeared at 853.5 ∘ C-949.7 ∘ C, and the exothermic peak represented the thermite reaction [19]. The differences of ignition temperature in the three studies are attributed to the diversity of materials and the difference of heating rate, but all three studies showed that thermite reaction Advances in Materials Science and Engineering needs high temperature (hundreds of degrees centigrade) to trigger.…”
Section: Reaction Behavior Under Quasi-static Compressionmentioning
confidence: 99%
“…But the heat generated by the reaction between Al and metal oxides (thermite) cannot be neglected. Zhou et al studied the reactions of Al/CuO, Al/Fe 2 O 3 , and Al/ZnO systems using T-Jump/time-of-flight mass spectrometer [10]. They found the temperatures of the reactions can reach 2837 K, 3135 K, and 1822 K, respectively.…”
Section: Introductionmentioning
confidence: 99%